Rechargeable adhesive with calcium phosphate nanoparticles inhibited long-term dentin demineralization in a biofilm-challenged environment. (January 2021) - Yu, Zhaohan; Tao, Siying; Xu, Hockin H.K.; Weir, Michael D.; Fan, Menglin; Liu, Yifang; Zhou, Xuedong; Liang, Kunneng; Li, Jiyao
Abstract: Objectives: This study aims to investigate the long-term demineralization-inhibition capability of a rechargeable adhesive with nanoparticles of amorphous calcium phosphate (NACP) on dentin in a biofilm-challenged environment. Methods: The NACP adhesive was immersed in a pH 4 solution to exhaust calcium (Ca) and phosphate (P) ions and then recharged with Ca and P ions. Dentin samples were demineralized under Streptococcus mutans biofilms for 24 h and randomly divided into two groups: (1) dentin control, (2) dentin with recharged NACP adhesives. Each day, all the samples were immersed in brain heart infusion broth with 1% sucrose (BHIS) for 4 h, and then in artificial saliva (AS) for 20 h. This cycle was repeated for 10 days. The pH of BHIS, the Ca and P ions content of the BHIS and AS were measured daily. After 10 days, the lactic acid production and colony-forming units of the biofilms were tested. The changes of remineralization/demineralization were also analyzed. Results: Dentin in the control group showed further demineralization. The recharged NACP adhesive neutralized acids, increasing the pH to above 5, and released large amounts of Ca and P ions each day. The recharged NACP adhesive decreased the production of lactic acid (P < 0.05), inhibited dentin demineralization and sustained the dentin hardness in the biofilm-challenged environment, showing an excellent long-term demineralization-inhibition capability. Conclusions: The NACP adhesive could continuously inhibit dentin demineralization in a biofilm-challenged environment by recharging with Ca and P ions. Significance: The rechargeable NACP adhesive could provide long-term dentin bond protection.